Economics for investment decision makers : micro, macro, and international economics - Piros, Christopher Dixon; Pinto, Jerald E. (CFA Institute investment series., 2013)
The economics background investors need to interpret global economic news distilled to the essential elements: A tool of choice for investment decision-makers. Written by a distinguished academics and practitioners selected and guided by CFA Institute, the world's largest association of finance professionals, Economics for Investment Decision Makers is unique in presenting microeconomics and macroeconomics with relevance to investors and investment analysts constantly in mind. The selection of fundamental topics is comprehensive, while coverage of topics such as inter.